2021
DOI: 10.3389/fmed.2021.729545
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia Intervention Trial (HIT): Study Protocol of a Randomized, Controlled, Parallel-Group Trial With Blinded Outcome Assessment

Abstract: Background: Hyponatremia is the most common electrolyte disorder with a prevalence of up to 30% in hospitalized patients. In contrast to acute hyponatremia where the need for immediate treatment is well-recognized, chronic hyponatremia is often considered not clinically relevant. This is illustrated by reports showing that appropriate laboratory tests are ordered in <50% of patients and that up to 75% are still hyponatremic at discharge. At the same time, emerging evidence suggests an association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Hyponatremia is commonly associated with higher mortality in hospitalized patients [23]. It remains, however, unclear whether hyponatremia by itself can contribute directly to mortality or is a marker for the severity of the underlying disease [24]. Although our study is unable to address causality, it is conceivable that hyponatremia—at least in part—contributes to morbidity and mortality by negatively affecting the disease course in acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 89%
“…Hyponatremia is commonly associated with higher mortality in hospitalized patients [23]. It remains, however, unclear whether hyponatremia by itself can contribute directly to mortality or is a marker for the severity of the underlying disease [24]. Although our study is unable to address causality, it is conceivable that hyponatremia—at least in part—contributes to morbidity and mortality by negatively affecting the disease course in acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 89%
“…Adult, hospitalised patients from all disciplines were included in the study (general medicine, geriatric medicine and surgical departments). The chosen time period was five years after the 2014 hyponatremia clinical practice guidelines and before the initiation of the "Hyponatremia Intervention Trial" (HIT) [37]. The HIT is an international, randomised, controlled, multicentre trial to study the effects of targeted correction of plasma sodium versus standard of care, which started at KSBL in April 2021 and could have been a bias to our audit.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…However, surprisingly, several studies have shown that once sodium levels drop below 120 mmol/L, there is no increase in mortality despite the worsening hyponatremia; instead mortality actually decreases. 10 One possible explanation for this observation is that patients who survive with very low PNa (<110 mmol/L) are usually hospitalized due to drug-induced hyponatremia rather than severe illness. On the other hand, hyponatremia of mild to moderate severity (≥120 mmol/L) tends to occur more frequently among patients admitted for life-threatening conditions, such as heart failure or cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…We eagerly await the results of the Targeted Correction of Plasma Sodium Levels in Hospitalized Patients with Hyponatremia (HIT) trial, an international multicenter randomized, controlled trial aiming to enroll 2278 hospitalized adult patients with PNa <130 mmol/L. 10 This study will compare mortality and 30-day rehospitalization in patients randomized to standard of care or targeted correction of hyponatremia following correction goals and limits recommended by the European clinical practice guidelines. However, the HIT trial may not be large enough to completely resolve the fast/slow correction debate.…”
Section: Introductionmentioning
confidence: 99%